2009
DOI: 10.1016/j.fcr.2009.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Yield losses of soybean and maize by competition with interseeded cover crops and weeds in organic-based cropping systems

Abstract: Weed management is a major issue in organic farming systems. Although interseeding cover crops is one alternative to herbicides, cover crops often suppress not only weeds but also main crops. Therefore, using cover crops for weed control without adverse effects on main crop growth is important. To verify the effect of cover crops on competition between main crops, cover crops and weeds in snowy-cold region, main crops soybean (Glycine max Merr.) in 2005 and maize (Zea mays L.) in 2006 were grown with cover cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 32 publications
3
54
1
Order By: Relevance
“…Jedrszczyk and Poniedziałek (2007) reported cover crops increased the content of corn dry matter in comparison to monoculture of corn in weedy condition. Uchino et al, (2009) resulted in increased coverage of corn, soybean and cover crop, declined weed dry matter. Weeds were suppressed effectively and stably without yield reductions of main crops by inter-seeded cover crops with sufficient fertilization in organic farming systems (Uchino et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jedrszczyk and Poniedziałek (2007) reported cover crops increased the content of corn dry matter in comparison to monoculture of corn in weedy condition. Uchino et al, (2009) resulted in increased coverage of corn, soybean and cover crop, declined weed dry matter. Weeds were suppressed effectively and stably without yield reductions of main crops by inter-seeded cover crops with sufficient fertilization in organic farming systems (Uchino et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, farmers interested in weed management have to rely on other control approaches (Hollander et al, 2007). An alternative weed control method is the use of cover crops (Uchino et al, 2009), which can suppress the growth of weeds by competition for light, soil moisture and nutrients, and also by producing allelopathic compounds (Compigla et al, 2010). Cover crops have been successfully integrated into conservational agriculture systems in many parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…However, winter rye residue cannot provide full-season weed suppression [16,17,21,22]. When used in an organic production system, winter rye has suppressed weeds through physical interference as a living mulch, but this system may also decrease crop grain yields [6,11,23]. Management of rye 2 International Journal of Agronomy using cultivation was necessary to minimize yield reductions, particularly in dry years, because no alternative methods exist to control rye in organic soybean.…”
Section: Introductionmentioning
confidence: 99%
“…4). The highest yield of soybean and maize was observed in treatment sowing of cover crops planted 21 days after sowing main crops (Uchino et al, 2009). Abdin et al (2000) also cited that maize grain yield in interseeded cover crop treatments was higher than maize pure stand under weedy conditions.…”
Section: Yield Of Maizementioning
confidence: 96%
“…In this treatment, the maximum intercepted light by maize was recorded at upper canopy layers. Uchino et al (2009) reported that intercepted light by main crop canopy reduced because most of the solar radiation was absorbed by upper canopy layers of weeds with high plant height. In addition, weed density and biomass decreased by reduction in available light (Bilalis et al, 2009).…”
Section: Absorbed Light Densitymentioning
confidence: 99%